Endoscopic full-thickness biopsy, a novel method in the work up of complicated abdominal symptoms. (8th January 2018) - Ohlsson, Bodil; Gustafsson, Rita; Swahn, Fredrik; Toth, Ervin; Veress, Béla; Thorlacius, Henrik
Gastrointestinal complaints without obvious organic causes confirmed by clinical laboratory analyses, endoscopy or radiology are often referred to functional entities. Irritable bowel syndrome (IBS) is the most common functional disorder in the gut. Careful examination of these patients may reveal other diagnoses of defined etiologies, e.g., enteric neuropathy, microscopic colitis, and primary Sjögre's syndrome. The present case describes a young patient with incapacitating gastrointestinal symptoms presumed to be IBS, who underwent endoscopic full-thickness biopsy in sigmoid colon. Histopathological examination revealed degenerative enteric neuropathy, possibly secondary to chronic ischemia.